Physicomechanical properties study of polyactic acid (PLA) in multi-single plane configurations via fused deposition modelling (FDM) - Lydia, Sandanasamy (2024)
One of the manufacturing processes included in this category of additive manufacturing (AM) is fused deposition modelling (FDM), and it is becoming popular among academics and business professionals for research and development. It is a sophisticated 3D printing technology for producing plastic materials, and this technique has recently risen in popularity as it is simple to use, inexpensive, and capable of processing thermoplastic polymers like acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), polycarbonate (PC) and nylon. The FDM method uses layer-by-layer melt-extrusion of a plastic filament to produce 3D structures. However, anisotropic properties are the major issue in the FDM printed parts that limits their applications. Therefore, this research aims to study the mechanical and physical properties of FDM-PLA printed samples by implementing multiplane layering. Hence, the implementation of multiplane was compared with single-plane layering. In order to achieve the goal, significant process parameters are identified with a thorough investigation of prior studies. In this research, the primary experiment is conducted by using Polylactic Acid (PLA) polymer. The mechanical properties are measured in terms of tensile strength and bending strength, whereas physical properties are measured in density and dimensional accuracy, respectively. Thus, the mechanical and physical properties of PLA printed samples were analysed by varying the building orientation and infill pattern. The experimental analysis shows that implementing multiplane has significantly enhanced the mechanical and physical properties of the FDM printed samples. The most significant parameter that affects the mechanical properties is building orientation. From the results, it can be seen that the tensile strength of multiplane (0°, 0°) of concentric and line patterns exhibits higher tensile strengths of 52.5 MPa and 51.0 MPa, respectively, compared to the single plane, which are 35.2 MPa and 30.2 MPa respectively. From the bending results, both concentric and lines pattern of building orientation 0° and 0° multiplane layering show higher results, 88.8 MPa and 88.3 MPa, compared to single-plane, which are 42.8 MPa and 46.0 MPa. Hence, the tensile strength results are proven in the morphology analysis. In comparing single and multiplane for the physical properties, density and dimensional accuracy, multiplane shows better results than single plane for density. In contrast, as for dimensional accuracy, both single-plane and multiplane are near their nominal value. In conclusion, this research has shown that implementing multiplane layering can significantly improve FDM printed PLA samples' mechanical and physical properties compared to single-plane layering. The study provides insight into the effects of processing parameters on the mechanical and physical properties of FDM printed parts, which can help optimise the process for better results. The findings of this research can be helpful in various fields that utilise FDM technology in line with sustainable development goals (SDG) goals particularly related to goal 9 that emphasize on industry, innovation and infrastructure with greater adoption of clean and environmentally sound technology, such as medical, automotive, aerospace, and consumer products. Furthermore, the technology can be utilised for a broader range of applications by improving the properties of FDM printed parts. This study contributes to advancing additive manufacturing technology and provides a better understanding of the potential benefits of implementing multiplane layering.